THE EFECTIVENESS OF CONTEXTUAL APPROACH IN TERMS OF CONCEPTUAL UNDERSTANDING AND LEARNING MOTIVATION OF JUNIOR HIGH SCHOOL STUDENTS - Dian Puspita; Sugiman . (Universitas Negeri Yogyakarta, 2016)
This study aimed to describe the effectiveness of contextual approach implementation using REACT strategy in terms of conceptual understanding and learning motivation of junior high school students in the learning of lines and angles. This research is a quasi experimental design with pretest-posttest control group design. The population includes all students of class VII in SMP Negeri 2 Depok. The selected sample is class VII A as an experimental class and class VII C as the control class. The instrument used in this study is test instrument used to measure understanding of mathematical concept which consists of pretest and posttest and nontest instruments in the form of questionnaire to measure students' motivation and learning observation sheets. Hypothesis testing method used was t test they are one sample t-test and independent sample t-test. The results showed that: 1) mathematics learning with contextual approach is effective in terms of conceptual understanding, 2) mathematics learning with contextual approach is effective in terms of student learning motivation, 3) mathematics learning with conventional approach effective in terms of conceptual understanding, 4) mathematics learning with conventional approaches effective in terms of student learning motivation, 5) contextual learning and conventional learning are effective in terms of conceptual understanding, and 6) contextual learning and conventional learning are effective in terms of learning motivation. Keywords: contextual approach, conceptual understanding, learning motivation, conventional approach